2012
DOI: 10.1177/1757975912453184
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and lifestyle characteristics associated with non-willingness to participate in health promotion programmes among adults of a lower socioeconomic status in Singapore

Abstract: Health promotion messages should adapt to the needs and situation of the disadvantaged, to increase participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“… ( p = 0.250). Ng CW (2012) [ 21 ] Cross-sectional From Jun to Oct 2009 Characteristic associated with non-willingness to participate in health promotion programmes Residents ≥18 y/o. 4 blocks of 1 to 2 rooms housing estate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… ( p = 0.250). Ng CW (2012) [ 21 ] Cross-sectional From Jun to Oct 2009 Characteristic associated with non-willingness to participate in health promotion programmes Residents ≥18 y/o. 4 blocks of 1 to 2 rooms housing estate.…”
Section: Resultsmentioning
confidence: 99%
“…Other reasons for not participating in screening were lack of time, misperceptions about screening (for example, they may feel that they were healthy or not at risk, hence it was not necessary) and lack of interest [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…More research is needed to identify the key factors driving these trends in these lower income rental flat communities and identify possible touchpoints for intervention. Generally, trends in health behaviours and participation in health screening should converge (Ng et al, ); a possible reason for the divergence noted in our study could be because the interventions in this community largely centred around promoting access‐enhanced health screening, with less focus on changing lifestyle behaviours.…”
Section: Discussionmentioning
confidence: 76%
“…These findings might be explained by a differing receptiveness to health education. One local study found that, among Chinese, Malays, and Indians, which are the three major ethnic groups in Singapore, Malays and Indians were more willing to participate in health education programs than the Chinese (25). Various degrees of language proficiency may also have played a role.…”
Section: Discussionmentioning
confidence: 99%